2003
DOI: 10.4028/www.scientific.net/msf.433-436.831
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Design of a SiC Schottky Barrier Diode Considering Reverse Leakage Current due to a Tunneling Process

Abstract: The optimization of the Schottky barrier height (SBH) and the maximum electric fields at the interface of a 4H-SiC Schottky barrier diode (SBD) is discussed, considering the reverse leakage current due to tunneling process. We first show that the reverse characteristics of a Ti/4H-SiC SBD are well described by the tunneling theory. Based on the tunneling theory, we show that the maximum electric field decreases as the Schottky barrier height decreases, and becomes smaller than the avalanche breakdown field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 2 publications
(3 reference statements)
0
15
0
1
Order By: Relevance
“…However, there is no consensus in literature on the model describing the reverse characteristics of 4H-SiC Schottky diodes. In fact, while some papers use the classical TFE model [34,42], whose validity depends on doping concentration and bias range [43], other works include the image force lowering effect in the TFE model to fit the experimental data [37,44].…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no consensus in literature on the model describing the reverse characteristics of 4H-SiC Schottky diodes. In fact, while some papers use the classical TFE model [34,42], whose validity depends on doping concentration and bias range [43], other works include the image force lowering effect in the TFE model to fit the experimental data [37,44].…”
Section: Resultsmentioning
confidence: 99%
“…In order to describe the experimental reverse characteristics I-V of SiC SBDs, several authors used the general model [6] of the tunneling current with [7][8][9][10][11] and without [5] the inclusion of the image force barrier lowering (IFBL). However, several authors [12][13][14][15][16][17] showed that the thermionic field emission (TFE) theory developed by Padovani-Stratton [18] can be used to describe the experimental reverse characteristics of SiC and other wide bandgap SBDs with and without the IFBL. Ivanov et al [19,20] and Lee et al [21] concluded that the thermionic emission model combined with the barrier lowering model is appropriate to describe the reverse characteristics I-V.…”
Section: Introductionmentioning
confidence: 99%
“…Combined and not combined with barrier lowering model, some authors [6][7][8][9][10][11] described the reverse leakage current using the general model [12] of the tunneling current. At the same time, the others [13][14][15][16][17][18] used the thermionic field emission (TFE) developed by Padovani-Stratton [19] also with and without the effect of the image force barrier lowering. However, some researchers [20][21][22] used thermionic emission model in combination with the barrier lowering one to describe the experimental reverse characteristics data.…”
Section: Introductionmentioning
confidence: 99%